Topographic Anatomy of the Inferior Medial Palpebral Artery and Its Relevance to the Pretarsal Roll Augmentation. Issue 3 (September 2016) - Cong, Li-Yao; Lee, Sang-Hee; Tansatit, Tanvaa; Hu, Kyung-Seok; Kim, Hee-Jin
Abstract : Background: A detailed analysis of the topography of the inferior medial palpebral artery is needed to optimize the safety and efficacy of pretarsal roll augmentation. Methods: Thirty-one hemifaces from 13 Korean and 8 Thai cadavers (15 male and six female cadavers) were dissected. The distributions of the inferior medial palpebral artery were determined with respect to the superior medial palpebral artery and the supratrochlear artery. Results: Four distribution patterns were observed. The inferior and superior medial palpebral arteries branched individually from the ophthalmic artery, with the ophthalmic artery terminating as the supratrochlear artery on the forehead (type I); a short trunk branched from the ophthalmic artery and divided into the inferior medial palpebral artery and superior medial palpebral artery, and the ophthalmic artery terminated as the supratrochlear artery (type II); the inferior and superior medial palpebral arteries arose together from the ophthalmic artery, and the ophthalmic artery terminated as the supratrochlear artery (type III); or the inferior and superior medial palpebral arteries were the terminal branches of the ophthalmic artery, with the supratrochlear artery arising from the angular artery (type IV). The diameter of the artery was 0.94 ± 0.22 mm at the entry point and 0.37 ± 0.11 mm at the lateral canthus. Conclusions: The inferior medial palpebral artery was located along the tarsal plate deep to the pretarsal part of the orbicularis oculi in the lower eyelid. Injections to augment the pretarsal roll should be made between the subcutaneous tissue and this pretarsal part of the orbicularis oculi.